Vegan candles - Reposeur, Delphine (Stackpole Books, 2022)
"Making your own candles allows you to choose ingredients that are healthy for you and for the planet. Even if it's your first time, you'll find success by following the instructions in this book. You'll learn: the materials and tools needed, and how to choose the best natural ingredients; the steps necessary to make both container and molded candles; 21 recipes with the scents to combine to make candles for a variety of moods."--